Spreadability of Five Vehicles on Five Surfaces. Issue 4 (September 2016) - Waldman, Alexandra; Kellen, Roselyn; Khattri, Saakshi
There are many factors that determine the type of vehicle chosen for a topical medication. Physician considerations include the body region where the agent will be applied, the thickness of the skin, and the amount of surface area in question. Patient considerations include ease of application and removal and aesthetic appeal. We compared the spreadability of five delivery systems used for topical medications (cream, lotion, ointment, gel, and foam) on five types of surfaces (synthetic skin, cardboard, aluminum foil, hard plastic, and soft plastic). In our study (for a set quantity of medication), the foam had the highest spreadability on all tested surfaces, and the ointment the lowest, with the foam covering nine times the surface area of the ointment. This quality makes foam agents ideal for large surface areas. Spreadability can help improve patient tolerability and compliance.